Improving the thickness distribution of parts with hybrid thermoforming - Duarte, F. M. (2022)
With the aim of improving the thickness gradient of thermoformed parts, and thus increase their performance and/or reduce their weight, the concept of hybrid thermoforming is introduced, whereby local thickness differences in extruded sheets are created prior to thermoforming. Material is removed by CO2 ablation or 3D printing of an over-thickness at specific locations of sheets previously extruded. The feasibility and potential usefulness of the approach is explored experimentally for the production of a truncated conical cup, since this is a well-characterized application. The conventional thickness distributions obtained by conventional vacuum forming are significantly changed with the new strategy and can be tuned by adequately selecting the locations and amount of material do be removed and/or added.